Economies of Scale and Natural Monopoly in the U.S. Local Telephone Industry - Sung, Nakil; Gort, Michael (The Review of Economics and Statistics, 2000)
This paper shows that firm-specific economies of scale—or net overall economies—are correlated with subadditivity. Both economies of scale and subadditivity are a decreasing function of firm size. Most firms are observed to be in the relatively flat portion of the long-run average cost curve, with pronounced economies of scale observable only at the low end of the scale. Economies of scope, as reflected in cost complementarities, do not appear to be a source of subadditivity. The results are estimated using translog total cost functions, and the fact that these cost functions include arguments for the quality of capital and of labor represents an innovation in methodology.